Nickel Industry In Japan - Masamichi Fujimori; Gen-ichi Nakazawa; Ichiro Doi (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
INTRODUCTION The major products of nickel industry in Japan are the electrolytic nickel (E-Ni), the ferro-nickel (Fe-Ni) and the nickel oxide sinter (NOS), totaling in production to 90 - 100 X 103 tons/year in terms of pure nickel content, and sharing approximately 20% for E-Ni, 10% or less for NOS, and the rest for Fe-Ni. The raw materials to be used for these products depend totally upon the imports from abroad; matte, the raw material used in the production of E-Ni, is from Australia and Indonesia; matte for the NOS is from Indonesia and New Caledonia; and garnierite, the raw material for Fe-Ni, is imported in bulk from New Caledonia, Indonesia and the Philippines. This report describes the acquisition of these raw materials, the production processes, trend of supply-demand, problem areas and the measures taken, and so forth, in connection with the nickel industry in Japan. ELECTROLYTIC NICKEL 1. History The nickel industry in Japan began in 1939 by the Sumitomo Metal Mining Co., Ltd. (SMM) with 150 tons E-Ni/month under the blast furnace smelting and the metal anode electrolysis. This was temporarily suspended after the end of last World War II, but resumed in 1952 with garnierite of New Caledonia as a raw material. Since then, the production capacity has been expanded incidentally to the increase of demand. However, since the smelting of garnierite contained about 2% nickel was very costly, the smelting process had been changed to smelt the briquettes of the mixture of garnierite and nickel sulfide concentrate imported from Canada and Australia. In 1975, this smelter was closed, and SMM's nickel refinery used matte from Western Mining Corp. (WMC) of Australia as a raw material. The refining process had been the metal anode one. The crude nickel oxide derived from roasting the high grade nickel matte had been melted and reduced with coke in the electric furnace and cast into anode. In 1970, a new refinery was constructed to produce 1,000 tons Ni/month under the matte anode process, and further, in 1976, the old refinery was converted into the matte anode process, thus resulting in the total production capacity of 1,690 tons Ni/ month today under the matte anode process. Shimura Kako Co., Ltd. began in 1951 to produce a little of E-Ni, and in 1955, they constructed a shaft furnace smelter with New Caledonian garnierite as a raw material to begin the E-Ni production under the matte anode process. Its monthly production reached 400 tons in 1957, but it discontinued its smeltering in 1963 to convert to the matte import from S. Le Nickel, WMC and INCO. In 1979, it changed the source of matte supply from the above to Soroako of Indonesia, discontinued the E-Ni production in 1979, and arranged for a total toll contract with Sumitomo. Meanwhile, SMM has developed a very distingished process for nickel-cobalt separation and refining by a solvent extraction method from nickel and cobalt mixed sulfide generated as a by-product in the nickel recovering process from laterite under the Nicaro process. Nippon Mining Co., Ltd. (NMC) also developed its own process. The plants under these processes were constructed in 1975, with the monthly production capacity of 230 tons of nickel and 130 tons of cobalt by SMM, and 300 tons of nickel and 110 tons of cobalt by NMC. SMM imports the raw material from the Marinduque Mining and Industrial Corp. of the Philippines, while NMC from Queensland Nickel Pty. Ltd. of Australia. 2. Production Status 2.1 Producers and materials Today, SMM holds the monthly E-Ni production capacity of 1,920 tons, of which 1,690 tons are from the matte anode process, and the remaining 230 tons are from the mixed sulfide as a raw material. NMC also uses the mixed sulfide as a raw material for a production of 300 tons/month. [ ] Most of SMM's raw material, nickel matte, is imported from WMC of Australia, partly using the Soroako matte from Indonesia. An example of material analysis is given in Table 1. Matte is a raw material for E-Ni and NOS, and the major sources of matte supply at present are Australian WMC and Indonesian Soroako, occupying ap-